Electrochromic cell with UV-curable electrolyte polymer for cohesion and strength - Soutar, Andrew M. (2013)
Electrically colourable (“electrochromic”) windows, hitherto confined to small areas, have recently been much expanded in area in new aircraft windows. Reviews indicate that to extend such high-tech applications to more everyday uses requires enhanced robustness, as in a new Prussian-Blue/polymer(Li+)/WO3 electrochromic device reported here. The new polymer electrolyte is UV-curable within the cell, obviating the need and risk of thermal polymerization while conferring mechanical robustness. Prussian Blue, (in reduced form the clear Prussian white “PW”, that is turned blue on electro-oxidation) and WO3 (showing a complementary clear-to-blue on electron uptake) are known to reliably undergo these established colourations as electrochromic anode and cathode, respectively.